DYNAMICS OF MEASLES ANTIBODIES IN HOSPITAL STAFF OVER A FIVE-YEAR PERIOD - Lyubov Denisovna Vlasova (Медицинская иммунология)
AbstractIntroduction. The incidence of measles has increased significantly worldwide in recent years. Measles virus is transmitted by aerosol and is highly contagious. Health care workers infected with measles are particularly at risk, as they may contribute to the hospital-acquired spread of infection. At the same time, medical personnel are at risk for contact with patients and biological material that may be infected with measles.The study objective - to study the dynamics of the content of anti-measles antibodies in health care workers over a five-year period.Materials and methods. Statistical processing of the results of enzyme-linked immunosorbent assay of blood serum of 272 health care workers of Clinics of Samara State Medical University aged from 22 to 62 years using StatTech v. 4.1.2. program was performed. The health care workers were divided into two age groups: from 22 to 44 years, from 45 to 62 years (average age 43 years). At the first stage of the study in 2018, the baseline level of specific anti-measles IgG was assessed. Individuals who demonstrated negative and questionable results were subjected to cleansing immunization. In the second stage of the study, specific antibody levels were re-assessed in 2023.Results. In both age groups, the average IgG concentration increased over the five-year period as a result of the 2018 revaccination (0.49 IU in 2023 vs. 0.20 IU in 2018). No statistically significant differences between age groups could be detected in 2018. By 2023, antibody concentrations were higher among those over 45 years of age. In the group without cleansing immunization, there was a decreasing trend in antibody values over the 5 years. The group with cleansing immunization showed an increase in positive results and a decrease in the proportion of negative and questionable results.Conclusion. Despite double injection of the anti-measles vaccine in childhood, not everyone is immune by adulthood. The 2018 cleansing immunization was generally quite effective. Individual characteristics of the organism, as well as a new coronavirus infection, may influence the formation of measles humoral immunity. Regular seromonitoring is necessary to monitor the maintenance of anti-measles humoral immunity, especially for those at risk, including health care workers.